Standardization of Waqf Accounting: A Systematic Review of Implementation and Its Challenges in Various Nations - Wali Saputra (INDO PUBLISHING, 2025)
This research endeavor seeks to systematically scrutinize the implementation processes and associated challenges pertaining to the standardization of waqf accounting across diverse nations. Employing the Systematic Literature Review (SLR) methodology, this investigation analyzed 22 meticulously selected scholarly articles disseminated between the years 2010 and 2025, sourced from the Scopus, ScienceDirect, and Google Scholar databases. The findings of the research indicate that a significant number of countries have yet to establish a standardized framework for waqf accounting, whereas Indonesia has emerged as a frontrunner by adopting PSAK 112. Principal challenges identified encompass the absence of specific regulatory frameworks, limited availability of qualified human resources, insufficient digitization of reporting mechanisms, and inadequate oversight and auditing systems. Additionally, the research uncovered substantial potential for the advancement of sharia-compliant waqf reporting standards, along with the application of innovative technologies such as blockchain to enhance transparency and accountability. The study advocates for the formulation of international waqf accounting standards, the fortification of human resource capabilities, and collaborative synergies among governmental entities, Islamic financial institutions, and academic circles to propel the global transformation of the waqf reporting paradigm